INOVASI PENGEMBANGAN BAURAN PEMASARAN DI CV BONEE ENGGENERING BANDUNG JAWA BARAT - andi, Andi; Supriyoso, Patria (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
Challenges faced by businesses in the era of open competition in Industry 4.0 must be anticipated accurately. Entrepreneurs are required to be creative, adaptive, and astute in addressing this phenomenon. They must be able to withstand shocks and grow stronger. The author chose the title "Innovation in Marketing Mix at CV Bonee Engineering." This research aims to analyze how the implementation of the marketing mix at CV Bonee Engineering forms its competitive advantage, making the company more competitive. It also aims to analyze the impact of innovation on business development at CV Bonee Engineering and assess whether the strategies implemented are suitable for the company. The research method used involves SWOT analysis and descriptive analysis with a qualitative approach. The author needs to understand the situation, conditions, and factual circumstances at CV Bonee Engineering, as well as internal and external factors influencing marketing strategies. Data collection techniques include interviews, observations, reference books, and journals. The collected data is carefully analyzed using SWOT analysis. The conclusion of this research is that the appropriate strategy for CV Bonee Engineering is the SO strategy (Strength-Opportunities), utilizing internal strengths to seize external opportunities. Customers can place orders according to their needs with a guarantee of faster processing time while maintaining quality. The WO strategy (Weaknesses-Opportunities) is also applied to minimize weaknesses by utilizing opportunities. The company promotes its services using technology and participates in various online marketplaces, remaining active on all social media platforms. The company continues to provide services, handle orders, negotiate prices, and collaborate on specific cases. Innovation positively impacts customer satisfaction and business development. Tactical steps for CV Bonee Engineering's innovation include building the right team, acting swiftly, and listening to customers.